2016
DOI: 10.1016/j.jpag.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Trainees to Deliver Adolescent Reproductive Health Services

Abstract: OBJECTIVE Delivery of reproductive services to adolescents varies by specialty and has been linked to differences in clinical training. Few studies have explored how different specialties’ graduate medical education (GME) programs prepare providers to deliver adolescent reproductive services. We explored the perceptions of resident physicians regarding their training in delivering adolescent reproductive health services. DESIGN Between November 2008 and February 2009, nine focus groups were conducted with gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Previous studies have found that general pediatricians report having concerns or discomfort about providing confidential consultation and care to adolescents for sensitive health issues. (6, 8, 23, 24) This discomfort with may help explain why general pediatric providers were less likely to endorse the provision of confidential consultation than board certified providers. It is also important to remember, as described in the methods, that visits with adolescent board certified providers differed from visits with general pediatric providers not only in terms of training, but also in terms of staffing and visit time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that general pediatricians report having concerns or discomfort about providing confidential consultation and care to adolescents for sensitive health issues. (6, 8, 23, 24) This discomfort with may help explain why general pediatric providers were less likely to endorse the provision of confidential consultation than board certified providers. It is also important to remember, as described in the methods, that visits with adolescent board certified providers differed from visits with general pediatric providers not only in terms of training, but also in terms of staffing and visit time.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, board certified adolescent medicine providers saw significantly more adolescents who self-reported health risk factors of substance use and sexual activity. Whereas general pediatric residents receive approximately one month of training in adolescent health rotations,(24) adolescent medicine board certified providers are required to have at least three years of full-time training in adolescent medicine. (25) Although no studies have been published showing that board certified providers are more likely to see high-risk patients, it is reasonable to conclude that high-risk patients are often referred to board certified providers – when available – due to their relative expertise and experience with sensitive adolescent health issues.…”
Section: Discussionmentioning
confidence: 99%